Experiment on Hunting Mechanism of Superheated Temperature of a Variable Refrigerant Volume Refrigeration System - Yu Zhongyang; Tao Leren; Wang Chao; Sheng Bingjie (Zhileng xuebao)
To experimentally investigate the hunting mechanism of superheated temperature of a variable refrigerant volume refrigeration system, the opening of electronic expansion valve, the capacity of chilled water and the outlet temperature of cooling water are changed. The results show that when the opening of electronic expansion valve is at 24.7 %-25.3 %, the humting amplitude of superheated temperature is less than 1 K. With the opening increasing (25.6%-26.2%), the humting amplitude is about 3 K. When the opening is at 26.5%-26.8%, the amplitude goes back to less than 1 K. Moreover, the change of heat transfer in evaporator is the primary cause to hunting of superheated temperature, and heating load and refrigerant mass flow are the important parameters for in-tube boiling heat transfer, and both of them should be considered in the investigation for hunting of superheated temperature. In addition, pressure ratio has greater effect on refrigerant mass flow. When the system is at the first stage of increasing pressure ratio, the mass flow rate of refrigerant also increases, and the surface coefficient of heat transfer sharply increases while superheated temperature decreases. When the pressure ratio is sequentially increasing, the mechanism of heat transfer keeps alternation between convective boiling of liquid film and heat transfer of superheated vapor. The mechanism of hunting of superheated temperature for closed-loop control of expansion valve-evaporator is more complicated, which should be focused in later research.